PENENTUAN NILAI SPF (SUN PROTECTING FACTOR) EKSTRAK ETANOL JAMUR KANCING (Agaricus bisporus) SECARA IN VITRO DENGAN METODE SPEKTROFOTOMETRI UV-VIS - Asriani Suhaenah; Masdiana Tahir; Nasra Nasra (As-Syifaa Jurnal Farmasi, 2019)
Chronic exposure to ultraviolet light from the sun will cause changes in skin structure and oxidative stress on the skin. The effects can be in the form of acute changes such as erythema, pigmentation and photosensitivity, as well as long-term effects of premature aging and skin damage. Sun Protection Factor (SPF) is a universal indicator that explains the effectiveness of a product or substance that is UV protection. Natural ingredients that can be used as UV protection are button mushrooms (Agaricus bisporus). This study aims to determine UV light protection activity in the ethanol extract of button mushrooms (Agaricus bisporus) based on the SPF values analyzed by UV-Vis spectrophotometry at wavelengths of 290-320 nm. The results showed that at concentrations of 1% and 2% had a medium SPF category with SPF values of 17,762 and 28,643. For concentrations of 3% and 4% it has a high SPF category with SPF values of 30,592 and 31,325. The higher the concentration used, the better the SPF value.